Comparison of total cost and outcomes between single-stage open reduction and Pemberton periacetabular osteotomy operation and two separate consecutive operations in treatment of bilateral developmental hip dysplasia in children at walking age - Ezirmik, Naci; Köse, Mehmet; Yılar, Sinan; Topal, Murat; Zencirli, Kemal (Ovid Technologies (Wolters Kluwer Health), 2020)
Open reduction and Pemberton periacetabular osteotomy (PPO) is one of the most preferred techniques for the treatment of developmental hip dyslaplasia (DDH) after the walking age. Performing the surgery as a one-stage operation or two separate consecutive operations is a controversial issue. In this study, we aimed to compare the outcomes, length of hospitalization and total cost between the patients whom had single-stage open reduction and PPO or two consecutive operations due to bilateral DDH in the walking age children. One hundred thirty patients with bilateral DDH had undergone open reduction and PPO for both hips. Seventy-five patients had one-stage open reduction and PPO for both of the hips, whereas 55 patients have two separate consecutive operations. Total time of exposure to anesthetics, blood loss and duration of operation were noted. Hospitalization period and total treatment costs were also noted for each patient. There was no statistically significant difference between the groups regarding the preoperative and postoperative AIs (P > 0.05). Comparing the total cost, length of hospitalization, exposure to anesthetics, perioperative blood loss, there was statistically significant difference between the groups (P < 0.005). Single-stage surgery had favorable outcomes. Major benefits of single-stage surgery for treatment of bilateral DDH are the reduced costs, anesthesia duration, intraoperative blood loss and hospitalization period. Also it can be presumed that prolonged immobilization can lead to loss of bone strength and resulting in fragility fractures. So single-stage open reduction and PPO for bilateral DDH can be preferred in experienced clinics.
Keywords: Male; Infant; Acetabulum; Walking; Osteotomy; Treatment Outcome; Child, Preschool; Developmental Dysplasia of the Hip; Humans; Female; Hospital Costs; Retrospective Studies; 3. Good health